The Effect of Melatonin Application and Watering Frequency on the Growth of Cocoa Seedlings (Theobroma cacao L.) - Zakariyya, Fakhrusy; Novelia, Eka Putri; Subroto, Gatot; Avivi, Sholeh (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Watering is one of the keys to cocoa plant growth, where proper watering enhances plant development, while infrequent watering can lead to drought stress. Melatonin can help mitigate the negative impacts caused by drought stress. Melatonin is a hormone that regulates various physiological processes and is believed to enhance plant tolerance to stress while stimulating growth. The purpose of this study is to investigate the effect of melatonin application on the growth of cocoa seedlings under different watering frequency. The study was arranged by randomized complete block design with a split-plot arrangement, consisting of two factors with three replications. The main plot represents watering frequency of 3 days, 6 days, and 9 days. The subplot represented melatonin concentrations of 0 ?M, 50 ?M, 100 ?M, and 150 ?M. Observational parameters included plant growth based on plant height, stem diameter, leaf number, and leaf area, as well as plant dry weight based on the dry weight of the shoot, roots, and total plant. The results showed that at the 3-day irrigation frequency, melatonin concentrations of 50-100 ?M enhanced plant growth parameters including plant height, stem diameter, leaf area, as well as shoot dry weight and total plant dry weight. At the 6-day frequency, melatonin application up to 150 ?M reduced growth and had no effect on total plant dry weight, but increased root dry weight. At the 9-day irrigation frequency with application of 150 ?M melatonin improved all growth parameters and total plant dry weight. Therefore, melatonin can enhance drought tolerance and promote plant growth under limited irrigation conditions.